An Analysis of Freedom of Speech: Whether the Indonesian Electronic Information and Transactions Law is Contradictory - Irrynta, Dwilani; Prasetyoningsih, Nanik (Faculty of Law, Universitas Pattimura, 2023)
Introduction: With the development of technology, people become easier in expressing themselves through social media. However, many people think that the Indonesian Government represses freedom of speech through the Electronic Information and Transactions (EIT) Law as the huge number of related cases keeps increasing, particularly on matters of criticizing the Government.Purposes of the Research: This article presents to discuss whether the Law does snatch the rights of citizens regarding freedom of speech as the Law essentially aims to protect such rights and shall not contradict the 1945 Constitution of the Republic of Indonesia stating that freedom of speech is a right for every citizen.Methods of the Research: By using normative legal research, this article examines legal principles and norms of related regulations. The authors analyze the situation faced by the Indonesian people in recent years through library research. The secondary data of literature was collected and reviewed focusing on the statutory approach along with the case approach.Results of the Research: The findings show that the EIT Law indeed draws controversy among Indonesian people due to the existence of several Articles under the Law that are contradictory to its purpose, namely protecting freedom of speech. By having ambiguousness and multiple interpretations of those several Articles, the Law leads to abuse of power by the Government. Therefore, it is reasonable for many people, as well as civil society organizations, to appeal to the Government to revise the Law and related regulations. It is on the grounds that such actions are necessary to enhance and enforce the protection of freedom of speech.